Analysing Employee’s Performance through Talent Management: The mediating role of Organizational Engagement. - Khalil, Syed Majid; Ihsan, Dr. Anjum; Khel, Dr. Shahid Jan Kaka (The journal of contemporary issues in business and government, 2022)
The current study examines on the relationship between talent management and employee performance. Theoretically, talent management is made up of six talent management (practices: talent planning, workplace culture, talent recruitment and retention, talent development, professional advancement, and rewarding. Despite its significance, our understanding of talent management is limited to how it affects employee performance. The current study aims to critically examine the relationship between talent management and work employee performance via the mediating role of organizational engagement. This study’s conceptual model of the Ability, Motivation, and Opportunity framework to better understand the mechanisms that facilitate the linkages between talent management, firm employee performance. The current study examined these underexplored relationships using Pakistan’s banking sector as a research study for developing markets. A questionnaire survey was used to collect data from 297 respondents of bankers in various departments to summarising the respondents’ opinions. To analyse the components of the hypothesised model, the current study used structural equation modelling techniques SEM-PLS. The current study’s findings discovered that organizational engagement facilitates the employee’s performance. Furthermore, organizational engagement in the company were found to be positively and significantly related to talent management. The current study’s findings might be valuable for businesses that emphasise the importance of organizational engagement in attaining improved employee performance through talent management in their organizations. This study contributes to understanding by putting the model to the test in the services industry and expanding talent management research to Asian emerging nations such as Pakistan. The theoretical contributions of the current study offer support for theorists of "best practices" or a universalistic approach to talent management rather than the best-fit approach; support for the assumptions underpinning support of the AMO model as a framework for developing a talent management system that integrates ability-enhancing employee planning and rewarding systems; and motivation-boosting professional advancement; and working environment and opportunity-enhancing retention and satisfaction practices, ultimately results in performance. It is one of the Pakistani studies that analyses the relationship between talent management, employee performance, so contributing to our understanding of emerging markets.